2019
DOI: 10.1002/cam4.2497
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors predisposing to cardia gastric adenocarcinoma: Insights and new perspectives

Abstract: Recent decades have seen an alarming increase in the incidence of cardia gastric adenocarcinoma (CGA) while noncardia gastric adenocarcinoma (NCGA) has decreased. In 2012, 260 000 CGA cases (age‐standardised rate (ASR); 3.3/100 000) and 691 000 NCGA cases (ASR; 8.8/100 000) were reported worldwide. Compared with women, men had greater rates for both the subsites, especially for CGA. Recently, four molecular subtypes of GC have been proposed by the Cancer Genome Atlas (TCGA) and the Asian Cancer Research Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 91 publications
(90 reference statements)
0
66
0
Order By: Relevance
“…pylori infection is one of the most common bacterial infections, affecting approximately half of the world population [1,2]. It can cause chronic gastritis, which in turn may be complicated with peptic ulcer disease, lymphoma, and gastric adenocarcinoma [3,4]. The major factor that affects the rates of cure from H. pylori infection is the sufficient inhibition of acid secretion using the anti-secretory agents such as proton pump inhibitors (PPIs) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…pylori infection is one of the most common bacterial infections, affecting approximately half of the world population [1,2]. It can cause chronic gastritis, which in turn may be complicated with peptic ulcer disease, lymphoma, and gastric adenocarcinoma [3,4]. The major factor that affects the rates of cure from H. pylori infection is the sufficient inhibition of acid secretion using the anti-secretory agents such as proton pump inhibitors (PPIs) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Development and progression of cancer is a complicated process, and many factors have been showed to contribute to the gastric carcinogenesis. Among them, systemic inflammatory response and nutritional status are two important contributors [21] . Evidences showed that CAR was an important inflammation-based prognostic indicator that associated with various cancer survival outcomes [22,23] .…”
Section: Discussionmentioning
confidence: 99%
“…We thus analyzed the transcriptome of stomach adenocarcinoma (STAD), which is the most common type of stomach cancer, 25 against the transcriptome of colon carcinoma (COAD).…”
Section: Rna-seq Analysis About Stomach Cancermentioning
confidence: 99%